Detection of cytosine deaminase in genetically modified tumor cells by specific antibodies - Haack, Karin; Moebius, Ulrich; Knebel Doeberitz, Magnus von; Herfarth, Christian; Schackert, Hans K.; Gebert, Johannes (Human gene therapy, 1997)
Bacterial cytosine deaminase (CD) converts the non-toxic prodrug 5-fluorocytosine (5-FC) into 5-fluorouracil (5-FU), which is toxic for mammalian cells. Therefore, the CD gene is used in cancer gene therapy to achieve high local concentration of a toxic metabolite without significant systemic toxicity. To allow the detection of CD expression at the protein level, we raised both polyclonal rabbit antisera and a monoclonal antibody (mAb) against a histidine-tagged CD fusion protein. The specificity of the polyclonal antisera and the mAb was confirmed by immunohistochemistry, immunoblot analysis, and immunoprecipitation using CD-expressing tumor cell lines. Furthermore, the antibodies can be used for ELISA assays and flow cytometry. Finally, the CD protein could be demonstrated in frozen tissue sections of CD-modified tumors in a rat tumor model using the anti-CD serum. With these antibodies, CD expression can now be monitored throughout in vitro and in vivo gene transfer studies, including clinical protocols relying on the CD suicide gene strategy.